American Academy of Pediatrics' Updated Clinical Guidelines for Managing Neonatal Hyperbilirubinemia. Issue 1 (January 2023) - Beal, Judy A.
Abstract : The American Academy of Pediatrics published updated clinical guidelines on management of hyperbilirubinemia for infants born at 35 weeks or more of gestation. Our pediatric nurse expert, Dr. Beal, explains the changes in clinical guidelines and their scientific rationale based on new evidence.